Two Regular Polygons with a Shared Vertex - Meskhishvili, Mamuka (Communications in Mathematics and Applications, 2022)
For two non-congruent regular polygons of the same type, the method of finding a point in the plane at the equal distances to the vertices, is established. The existence of two points with this property is proved for two polygons with a shared vertex. For one of them, it is proved that it satisfies the Bottema theorem conditions and based on this, the generalized Bottema theorem for any two regular polygons is given.